2007
DOI: 10.1021/jo062491x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the PalladiumII-Catalyzed Hydroxyalkoxylation of 2-Allylphenols

Abstract: The Pd(OCOCF3)2/[(HOCH2CH2NHCOCH2)2NCH2]2-catalyzed oxidation of o-allylphenol with H2O2 in water/methanol affords a syn and anti mixture of 2-(1,2-dihydroxypropyl)phenol and 2-(2-hydroxy-1-methoxypropyl)phenol. Mechanistic experiments and ESI-MS studies support a pathway wherein isomerization of the C=C bond followed by its epoxidation and oxirane opening led to the products. Recycling of the catalytic system led to gradual lost of activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…With regards the underlying mechanism, if the reactions proceeded via a p-allyl-palladium intermediate, seven-membered heterocycles would also have been formed, in accord with the results of Beccalli et al [4] In view of the marked difference between the electron density of the tosyl-protected aniline-type nitrogen and the protected cyclohexylaminetype nitrogen, we suggest that, after a Pd-mediated double bond migration, [9,10] the ring-closure towards 9-13 and 17 takes place via cis-aminopalladation, [1k] due to the stronger coordination of the protected cyclohexylamine-type nitrogen to the palladium moiety. (Scheme 4).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…With regards the underlying mechanism, if the reactions proceeded via a p-allyl-palladium intermediate, seven-membered heterocycles would also have been formed, in accord with the results of Beccalli et al [4] In view of the marked difference between the electron density of the tosyl-protected aniline-type nitrogen and the protected cyclohexylaminetype nitrogen, we suggest that, after a Pd-mediated double bond migration, [9,10] the ring-closure towards 9-13 and 17 takes place via cis-aminopalladation, [1k] due to the stronger coordination of the protected cyclohexylamine-type nitrogen to the palladium moiety. (Scheme 4).…”
Section: Resultssupporting
confidence: 88%
“…The combined organic phase was dried over anhydrous Na 2 SO 4 and evaporated to dryness under reduced pressure. The residue was purified by column chromatography (n-hexane/ethyl acetate 4:1), which provided pure compounds 9-15, 17, 18, 23 and 24. (2R * ,4aR -vinyl-2,3,4a,5,6,7,8,8a-octahydro-1H-quinazolin-4-one (9) 4, 24.7, 24.9, 30.9, 39.9, 45.3, 53.0, 69.8, 117.5, 119.9, 126.8, 130.1, 132.4, 136.4, 136.9, 144.0, 166.7 ppm;IR (KBr): ñ = 3079, 2960, 2942, 2865, 1935, 1655, 1445, 1343, 1246, 1168, 1090 14,H 7.00,N 7.48;found: C 64.02,H 7.12,2,6a,7,8,9,10, 4, 23.9, 24.9, 28.6, 28.7, 41.9, 44.4, 49.4, 58.2, 117.1, 118.1, 126.9, 127.0, 130.3, 134.1, 138.8, 143.4, 171.8 ppm;IR (KBr): ñ = 3085, 3067, 2924, 2864, 1935, 1834, 1654, 1445, 1396, 1336, 1221, 1154, 1090 14,H 7.00,N 7.48;found: C 64.01,H 6.82,3,6a,7,8,9,10, -4,6-dione (24): Pr...…”
Section: Experimental Section General Methodsmentioning
confidence: 99%
“…[34] A similar epoxide opening was observed with 2-[2-(benzyloxy)phenyl]-3-methyloxirane [Equation (14)]. [33] …”
Section: Water and Alcohol Additionmentioning
confidence: 62%
“…The Pd II -catalyzed oxidation of (E)-2-(prop-1-enyl)phenol with H 2 O 2 in aqueous methanol affords a mixture of 2-(1,2-dihydroxypropyl)phenol and 2-(2-hydroxy-1-methoxypropyl)phenol [Equation (13)]. [32] We demonstrated that this reaction involves the formation of an epoxide as the intermediate; [33] this was favored by the phenolic OH. [34] A similar epoxide opening was observed with 2-[2-(benzyloxy)phenyl]-3-methyloxirane [Equation (14)].…”
Section: Water and Alcohol Additionmentioning
confidence: 99%
See 1 more Smart Citation